Las artes plásticas y la coordinación visomotriz en los niños de 3 a 4 años de la Unidad Educativa del Milenio Bernardo Valdivieso de la ciudad de Loja, en el periodo 2022 - 2023 - Carrillo Ramos, Nathaly Dayana (2023)
Visual-motor coordination are movements executed by some part of the body coordinated with the eyes, which allows to carry out daily activities by children, being of great importance their stimulation and optimal development. The objective of this research work is to determine the impact of plastic arts for the development of eye-motor coordination in children from 3 to 4 years of the Unidad Educativa del Milenio Bernardo Valdivieso of the city of Loja, period 2022-2023. The research design was pre-experimental with a quantitative approach and a descriptive scope. The study population was made up of twenty children selected through a non-probabilistic sampling. The methods used were: analytical-synthetic, inductive and deductive. For the initial and final diagnosis of the development level of visuomotor coordination, the coordination subtest of the Psychomotor Development Test TEPSI was applied. The results of the initial evaluation reflected that: 55% of the children were at risk and only 20% were normal. For this reason, a guide of twenty-five activities called "My little box of creativity" was designed, once applied, a significant improvement was evidenced, achieving that: 65% of the children were located at the normal level and 20% at risk. Concluding that the plastic arts significantly contribute to areas of development of children, thanks to the use of them, a large part of the infants managed to acquire greater control of movements with their hands, optimal coordination and precision to perform them, demonstrating the great influence of the plastic arts in visuomotor maturation. Keywords: visual motor coordination, controlled movements, painting, drawing and modeling